Treatment of Post-Cardiopulmonary Bypass SIRS by Hemoadsorption: A Case Series. Issue 3 (March 2016) - Träger, Karl; Fritzler, Daniel; Fischer, Guenther; Schröder, Janpeter; Skrabal, Christian; Liebold, Andreas; Reinelt, Helmut
The use of cardiopulmonary bypass (CPB) in cardiothoracic surgery results in a well-known activation of the immunologic response. In some cases, however, this triggered immunologic response may be excessive, leading to a severe systemic inflammatory response syndrome (SIRS) and induced organ dysfunction. For example, patients frequently develop hemodynamic instability with hypotension and low systemic vascular resistance. To date, different therapeutic approaches, such as steroids, have been tried to control this maladaptive postoperative SIRS response, yet definitive proof of clinical efficacy is missing. A new cytokine adsorber device (CytoSorb; CytoSorbents) may be a useful approach to control hyperinflammatory systemic reactions by reducing a broad range of proinflammatory cytokines and other inflammatory mediators. This may, in turn, help to reestablish a physiologic immune response and help to restore deranged clinical parameters in these patients. In this retrospective case series study, we describe 16 cardiac surgery patients following prolonged CPB with post-CPB SIRS and subsequent acute kidney injury, who were then treated with hemoadsorption using CytoSorb in combination with continuous renal replacement therapy (CRRT). Treatment of patients with CytoSorb who presented with severe post-CPB SIRS resulted in a reduction of elevated cytokine levels, which was associated with a clear stabilization of deranged hemodynamic, metabolic, and organ function parameters. Treatment was well tolerated and safe, with no device-related adverse events occurring. CytoSorb therapy combined with CRRT is a potentially promising new treatment approach to achieve hemodynamic stability, cytokine reduction, and improved organ function in cardiac surgery patients who develop post-CPB SIRS.